Earthen construction in Puerto Rico? Buried knowledge, interrupted wisdom (2019)
In Puerto Rico, there is evidence of two earth constructions for the 16th century. The technique used was rammed earth. This knowledge did not proliferate or evolve, in fact, today there are no modern constructions made on earth. The average of Puerto Rican does not know about earth constructions and due to this inexperience there is much skepticism about the frequency of hurricanes, high precipitation and being prone to earthquakes / tsunamis. The relevance of finding historical precedents in Puerto Rico would help to understand their behavior over time. Countless research indicates that these constructions have been effective in places with similar conditions those the island. In the era of climate change, it is important to obtain this ancestral knowledge of materials that have solved the need for housing with a low environmental impact. After the passage of the last hurricane Maria, Puerto Rico faced the reality that exists when we understand the dependence on fossil and non-renewable energy, the importation by ship of building materials and the exercise of recovering from the government (top to bottom), It is very fragile and susceptible. Through a search of the documentation in Historical Archives, it was possible to locate and obtain information on the earth construction. According to several sources of scientific research, it is possible to face environmental problems based on the knowledge that empowers from the town and with adjustments in our lifestyle, it was understood that the limitations are in the ignorance.